Effect of Heteroatom and Charge Reconstruction in Atomically Precise Metal Nanoclusters on Electrochemical Synthesis of Ammonia. (14th April 2022) - Han, Meng; Guo, Minghao; Yun, Yapei; Xu, Yujun; Sheng, Hongting; Chen, Yanxia; Du, Yuanxin; Ni, Kun; Zhu, Yanwu; Zhu, Manzhou
Abstract: Although atomically precise metal nanoclusters (NCs) are widely used in catalysis, a wide gap exists between state‐of‐the‐art performance and practical requirements. Regulating the intrinsic activity of NCs is critical for the rational design and synthesis of highly efficient catalysts. Herein, M4 Ni2 NCs (M = Au, Ag) with improved electrocatalytic nitrogen reduction reaction (NRR) activity due to the introduction of Ni are synthesized, which significantly suppresses the H2 generation competition reaction. Ag4 Ni2 NCs exhibit the best NRR activity at −0.2 V versus RHE with a NH3 yield of 23.32 µg mg –1 h –1 and a faradic efficiency of 78.97% due to the higher N2 chemisorption ability and lower rate‐determining barrier. Meanwhile, ligand partial detachment of NCs during electrocatalysis offers exposed active sites and induces the charge reconstruction, also contributing to the outstanding NRR performance. Based on the precise composition and structure, deep insights into the NRR mechanism at the atom level are provided by in situ Fourier‐transformed infrared spectroscopy and ab initial calculation. The study presents an efficient strategy based on heteroatom doping and charges reconstruction to promote NCs catalytic performance. Abstract : M4 Ni2 nanoclusters (NCs) (M = Au, Ag) with improved electrocatalytic nitrogen reduction reaction (NRR) activity due to the introduction of Ni is synthesized, which significantly suppresses the H2 generation competition reaction. By ligand partial detachment during the electrocatalysis process, M4 Ni2 NCs expose active sites and induce the charge reconstruction, also contributing to the outstanding NRR performance.